KONDISI EKOSISTEM DAN VALUASI EKONOMI LAMUN DI PANTAI SAMUH, NUSA DUA, BALI - Lazaren, Cornelia Coraima; Antara, Made; Astarini, Ida Ayu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 2 (2020)DO - 10.24843/EJES.2020.v14.i02.p10, 2020)
Seagrass ecosystems in addition to providing economic benefits also have ecological functions, so it is highly recommended to conserve these ecosystems in order to preserve spawning areas, nurseries and habitats for fish and other marine biota. This study aims to identify the condition of seagrass ecosystems in Samuh Beach, Nusa Dua, estimating the economic value of the seagrass ecosystems in Samuh Beach, Nusa Dua and formulating for sustainable management of seagrass ecosystems in Samuh Beach, Nusa Dua. The study was conducted in January-March 2020 at Samuh Beach, Nusa Dua, Bali. Data collected includes secondary data and primary data. Secondary data were collected from related institutions, while primary data were collected through purposive sampling and questionnaires. The analysis used was description analysis, calculation of the economic value of marine resources through a Total Economic Value (TEV) and DPSIR analysis. This study found that the actual condition of the seagrass ecosystem resources in Samuh Beach is currently in the category of less rich/less healthy due to natural factors (substrate conditions) and human activity (anthropogenic). The economic value of seagrass ecosystems at Samuh Beach Nusa Dua, Bali showed the total economic value reached IDR. 327,843,325 per year and seagrass ecosystem management strategies that can be applied in the coastal area of ??Samuh Beach are the development of marine ecotourism, stock enrichment, and rehabilitation of seagrass beds. Keywords: Seagrass condition; TEV; economic valuation; Samuh beach.